Interaction between mechanosensitive channels embedded in lipid membrane. (March 2020) - Zhu, Liangliang; Zhao, Wei; Yan, Yuan; Liao, Xiangbiao; Bourtsalas, Athanasios; Dan, Yong; Xiao, Hang; Chen, Xi
Abstract: The study of the gating mechanism of mechanosensitive channels opens a window to the exploration of how different mechanical stimuli induce adaptive cellular behaviors of both the protein and the lipid, across different time and length scales. In this work, through a molecular dynamics-decorated finite element method (MDeFEM), the gating behavior of mechanosensitive channels of small conductance (MscS) in Escherichia coli ( E. coli ) is studied upon membrane stretch or global bending. The local membrane curvature around MscS is incorporated, as well as multiple MscL (mechanosensitive channels of large conductance) molecules in proximity to MscS. The local membrane curvature is found to delay MscS opening and diminishes moderately upon membrane stretching. Mimicking the insertion of lysophosphatidylcholine (LPC) molecules into the lipid, both downward and upward bending can active MscS, as long as the global membrane curvature radius reaches 34 nm. Based on the different MscS pore evolutions observed with the presence of one or more MscLs nearby, we propose that when coreconstituted, multiple MscL molecules tend to be located at the local membrane curvature zone around MscS. In another word, as MscL "swims around" in the lipid bilayer, it can be trapped by the membrane's local curvature. Collectively, the current study provides valuable insights into the interplay between mechanosensitive channels and lipid membrane at structural and physical levels, and specific predictions are proposed for further experimental investigations. Graphical abstract: Image 1 Highlights: Local membrane curvature around MscS delays its opening. Local membrane curvature around MscS diminishes upon membrane stretching. Both downward and upward bending of the membrane can active MscS. The presence of MscL near MscS delays its opening. MscL can be trapped by the local membrane curvature around MscS.